Diagnostic Assessment of Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs)
Diagnostic methods of assessment of the child with status epilepticus (SE) are outlined following an evidence-based review of literature by the Quality Standards Subcommittee of the AAN and Practice Committee of the CNS.